Profiling autoantibodies in chronic obstructive pulmonary disease using antigen microarray technology - Shindi, Reham (2016)
Chronic obstructive pulmonary disease (COPD) encompasses the diseases of chronic bronchitis and emphysema, both of which can cause the main feature of this disease; airflow obstruction. COPD is the third leading cause of mortality in the world, and although cigarette smoking is the main risk factor of the disease, other environmental factors and genetic disorders can also play a role. The pathogenesis of COPD is currently still poorly documented, which results in poor diagnosis and treatment for the disease. The involvement of autoimmunity in the pathogenesis of the COPD is becoming more apparent; in recent studies, high levels of circulating autoantibodies have been detected in patients with COPD, suggesting that this lung disorder may have an autoimmune component. Therefore, research has focused on identifying a set of autoantigens known to be associated with other autoimmune disorders that may play a role in the pathogenesis of this disease.